Analisis Kelelahan Kerja pada Departemen Machining dan Fabrikasi dengan NASA-TLX dan Subjective Self Rating Test - Ayuningtyas, Wulan; Herwanto, Dene; Gemilang Putra, Candra Galang (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2021)
During the Covid-19 pandemic, production operators at PT. Riken Engineering Perkasa is required to complete work on time, resulting in the operator working longer hours and less rest time. PT. Riken Engineering Perkasa has a 6-day work system, has a working time of 9 hours/day with a break of 1 hour/day, except for Saturdays when it is 5 hours/day. In this case, the operator may have a work accident and do the same job repeatedly due to a defect in the product. Who conducted this research on production operators in the Machining and Fabrication department of PT. Riken Engineering Perkasa aims to analyze all production operators' work fatigue and mental workload during the Covid-19 pandemic. This research was conducted using the NASA-TLX method and the Subjective Self Rating Test. The mental workload of the very high indicator category was four operators, the high indicator category value was eight operators, and the low indicator category value was one operator. As for work fatigue, the average score for the medium category is eight operators, and the average value for the standard type is five operators. It can be concluded from the mental workload and work fatigue at PT. Riken Engineering Perkasa in the Machining and Fabrication department has a reasonably high category score; the results of these studies can be used as a reference for actions taken by PT. Riken Engineering Perkasa reduces mental workload and fatigue on operators by changing operator shifts and increasing rest hours. So that these operators can achieve optimal productivity with the quality of the products produced remains stable and maintained